Rational belief or poetical satisfaction - Dougherty, Jude P. (Sapientia, 2001)
The highly positive reception accorded John Paul II's Fides et Ratio, indeed the attention given by the secular media to most of his writings, attests to the need that many have for spiritual nourishment as the intellectual and cultural influence of religion wanes in a country once thought to be Christian. The decline has been long in the making and mirrors the European experience of the past century. The Spanish-born, Harvard University professor George Santayana, writing in 1937 for an American audience, observed: The present age is a critical one and interesting to live in. The civilization characteristic of Christendom has not disappeared, yet another civilization has begun to take its place. We still understand the value of religious faith [...] On the other hand the shell of Christendom is broken. The unconquerable mind of the East, the pagan past, the industrial socialistic future confront it with equal authority. Our whole life and mind is saturated with the slow upward filtration of a new spirit —that of an emancipated, atheistic, international democracy1 . In the early decades of this century that type of judgment may have required the perceptiveness of a Santayana. Today it is universally acknowledged.